Economic Security of an Enterprise is the Way to Financial Stability - M. A. Polyakova; S. A. Barbashova; I. E. Ekaterinina (Учёт. Анализ. Аудит)
In modern economic conditions, business entities are increasingly paying attention to the issues of economic security, which allows businessmen to regularly monitor and control the state of financial stability. The vector of the direction of stable economic development of an economic entity has recently become increasingly important among entrepreneurs and is manifested through the introduction of elements of economic security into the system of financial and economic activity. Safe entrepreneurial activity is an important and necessary condition for healthy competition and sustainable development of a business entity of any form of ownership, regardless of the type of activity carried out. The economic security of an enterprise should be considered as a multifaceted category consisting of internal and external factors and risks. The article highlights the problem of insufficient implementation of the existing mechanism of functioning at the enterprise PJSC “Penzkompressormash” of economic security and, as a consequence, the deterioration of the financial stability of the business entity. The purpose of the study is to substantiate the importance of economic security in entrepreneurial activity of any form of ownership, through solving the tasks set: analysis and assessment of financial stability, identification of «bottlenecks» and ranking them by causes of occurrence; search for reserves to improve the financial condition of the company, its solvency and financial stability; development of specific measures aimed at more effective use of financial resources and strengthening the economic condition of the enterprise. In the course of the research, the authors used such scientific methods as comprehensive and comparative analysis, generalization, synthesized and economic-statistical approaches. The basis of the theoretical methodology was formed from the works of modern scientists and economists, legislative acts of the Russian Federation, official publications, materials of scientific and practical conferences, etc. The article contains proposals for the use of elements of economic security as a necessity to bring an enterprise out of a difficult financial situation.